Who knows best? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
After ordering two books from CTA on Alternative Financing , Malamine Kamara, secretary of the credit and savings association of Sedhiou, Senegal, tells us 'they have become valuable tools for our work. We have noticed how a lot of the experts we...